IMPACT OF PRE-OPERATIVE REHABILITATION ON POSTSURGICAL COMPLICATIONS AND RECOVERY - Khalid Ahmed Ali Alawi, Mohsen Ayed Shabab Albaqami, Jafar Abdullah Ali Abu Qurain, Ahmed Salman Habib Al Ajmi, Muslem Fouad Abdullah Almuslem, Abdullah Mohammed Ali Altaher (Chelonian Research Foundation, 2022)
Pre-operative rehabilitation, or prehabilitation, has emerged as a promising strategy to improve post-surgical outcomes and reduce complications. This study aimed to investigate the impact of prehabilitation on postsurgical complications and recovery among patients undergoing various surgical procedures. A systematic review and meta-analysis were conducted, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomized controlled trials (RCTs) comparing prehabilitation with standard care were included. The primary outcomes were postsurgical complications and length of hospital stay (LOS). Secondary outcomes included functional capacity, quality of life (QoL), and pain. Random-effects meta-analyses were performed to calculate pooled effect sizes. Twenty-eight RCTs, involving 3,542 patients, were included. Prehabilitation significantly reduced the risk of postsurgical complications (risk ratio [RR] = 0.68, 95% confidence interval [CI]: 0.57-0.81, p < 0.001) and LOS (mean difference [MD] = -1.82 days, 95% CI: -2.41 to -1.23, p < 0.001) compared to standard care. Prehabilitation also improved functional capacity (standardized mean difference [SMD] = 0.45, 95% CI: 0.26-0.64, p < 0.001), QoL (SMD = 0.29, 95% CI: 0.14-0.44, p < 0.001), and pain (MD = -0.79, 95% CI: -1.14 to -0.44, p < 0.001) after surgery. The findings suggest that prehabilitation is an effective strategy to reduce postsurgical complications, shorten hospital stay, and improve functional outcomes and QoL in patients undergoing surgery. Keywords: prehabilitation, pre-operative rehabilitation, postsurgical complications, recovery, systematic review, meta-analysis